Gogmagog : a first chronicle of Ludwich - Noon, Jeff; Beard, Steve, 1961- (Chronicles of Ludwich, 2024)
"Meet Cady Meade, captain of the steam-launch, Juniper. In her heyday she carried people and goods on the river Nysis, from the thriving seaports of the estuary into Ludwich, the capital city. But that was years ago. Now she's drunk, holed up in a rundown seaside resort, telling her bawdy tales for shots of rum. All this changes, when two strangers seek her out, asking for transports: a young girl, very ill, and in grave danger, and an artificial being of singular character with secrets hidden inside his crystal skull. But the Nysis is unlike any other river. Few can navigate its channels, whirlpools and sandbanks; few know of the ravenous creatures that lurk beneath the surface. And Cady's glory days are well behind her now..."--